Harassment among people on the web. an analysis of netizens’ responses to Patson Dzamara’s posts with regards to the disapperance of Itai Dzamara. - Ndavambi, Victoria K. (Midlands State University, 2017)
This study set out to explore the discourses embedded in netizens’ responses to Patson Dzamara’s facebook posts with regards to the disappearance of Itai Dzamara. It sought to describe and explain how the netizens read and interpreted these posts. In other words it explores the issues raised by netizens and the rationality of their discussions. The researcher purposively selected the posts with regards to the disappearance of Itai Dzamara on Patson Dzamara’s Facebook page, and their corresponding responses. The posts were subjected to critical discourses analyses and semiotic analysis, whilst the findings were thematically presented. This research found out that the netizens participated extensively in the discussions with regards to the disappearance of Itai Dzamara. Itai Dzamara was portrayed as the selfless gallant son of Zimbabwe while the fellow Zimbabweans were labelled as cowards. President Mugabe and ZANU PF were labelled as Boko Haram whilst the church was castigated for being complicit in the oppression of Zimbabweans. Finally the study established that, the difficulty in establishing respondents’ true identity led some of the respondents to be unrestrained in their attacks on President Mugabe and ZANU PF.